Intensification of “mola” (Amblypharyngodon mola) culture in homestead ponds - Mona, SN; Sultana, S; Ahmed, KK; Khan, N; Huq, KA; Mojumder, P (International Journal of Agricultural Research, Innovation and Technology, 2020)
The research was carried out with small indigenous fish species (SIS) named mola (Amblypharyngadan mola) in monoculture system to intensify production in farmers’ homestead ponds with 50% household women involvement during June to December, 2016. Brood mola was stocked at the rate of 2, 4 and 6 m-2 with three replications in each treatment. Supplementary feed (27.1% protein) consisted of commonly available agricultural by-products was provided daily at the rate of 2% of the total biomass along with natural feed as mola is planktivorous species. Seven different water quality parameters were measured fortnightly and found within cultivable range. Gross production of mola were obtained 520.59±23.4, 599.06±258.87, 1063.94±42.87 kg ha-1 from T1, T2 and T3, respectively after 4 months’ culture period. The yield of T3 was significantly greater (P < 0.05) than T1 and T2. The highest gross production was obtained in T3 where stocking density was 6 brood mola m-2. Int. J. Agril. Res. Innov. Tech. 9(2): 23-29, December 2019